Cardiovascular risk among patients recovered from COVID-19 in the short and medium term: what does the current evidence conclude? - Picón Jaimes, Yelson Alejandro (2023)
Cardiovascular risk and diseases among patients recovered from COVID-19 is a recent field of study in the world medical literature and is also of vital importance because a large number of patients develop complications once the acute phase of the disease is over. The broad spectrum of myocardial injury in cardiovascular diseases can range from theasymptomatic elevation of cardiac troponin levels to the development of fulminant myocarditis and/or circulatory shock, which can leave significant sequelae. Despite the fact that there is no clear strategy to treat cardiac events that occur during COVID-19 infection and taking into account that treatment is mainly aimed at relieving patients’ symptoms as they arise, the objective of this work was to find out and collect current evidence on this subject, so that readers can be offered a reference guide in Spanish that contributes to the development of their health profession. The methodology used was a literature search in databases including Medline, Scopus and ScienceDirect within a time window between 2019 and 2022. The main results revealed that the molecular and pathophysiological mechanisms involved in post-COVID-19 syndrome include the renin-angiotensin-aldosterone system since SARS-CoV-2 tropism is linked to angiotensin-converting enzyme 2. This causes an alteration of the neurohumoral response of the cardiovascular, renal and digestive systems,generating deficits in the signaling pathways and causing direct damage to the heart, lungs and other organs. Post-COVID-19 syndrome, in general, is defined as the occurrence or persistence of symptoms three or four weeks after the acute phase of the disease. This could then be considered as a time window of risk and strict follow-up to assess in apersonalized way the risk among the different groups of patients, especially those with a past history of cardiovascular disease. The main results revealed disorders such as heart failure, arrhythmias, pericarditis and myocarditis, which require early detection and occur days or even weeks after the acute phase of COVID-19.